Enterprise Architecture Design in the General Affair Division of Telkomsel Bali Nusa Tenggara with TOGAF ADM - Putu Eternalie Prajnani Welaga; Anak Agung Ngurah Hary Susila; Putu Veda Andreyana; Berkat Samuel Gunawan Naibaho (Institute for Research and Community Services Udayana University, 2025)
Telkomsel Bali Nusa Tenggara is one of the regions owned by Telkomsel. In each region, there is a General Affair division that is responsible for managing the company's operational needs. In supporting existing activities, the General Affair division already has an information system. However, there are still business processes that are carried out manually and there are no information system design guidelines for the General Affair division. Therefore, it is necessary to design enterprise architecture using TOGAF ADM with eight phases consisting of Preliminary Phase, Requirement Management, Architecture Vision, Business Architecture, Information System Architecture, Technology Architecture, Opportunities and Solutions and Migration Planning. The purpose of this research is to create a division architecture design that is in accordance with the company's vision and mission. Data was collected using observation method, interview method and document analysis. The results obtained are the target architecture design and blueprint.